The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/09546553.2019.1634559
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with Online Extremist Material: Experimental Evidence

Abstract: Despite calls from governments to clamp down on violent extremist material in the online sphere, in the name of preventing radicalisation and therefore terrorism research investigating how people engage with extremist material online is surprisingly scarce. The current paper addresses this gap in knowledge with an online experiment. A fictional extremist webpage was designed and (student) participants chose how to engage with it.. A mortality salience prime (being primed to think of death) was also included. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Other studies were excluded as it was identified that a media‐related factor was not in fact the treatment component of the study. For example, Reeve (2019) used a fictional extremist website as the exposure condition, in which all participants accessed the website and the treatment was a mortality salience prime, which was assessed for its effects on participants' interactions with the site. Lemieux and Asal (2010) used a vignette design in which participants were asked to take a first‐person perspective as a member of a fictional ethnic minority.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies were excluded as it was identified that a media‐related factor was not in fact the treatment component of the study. For example, Reeve (2019) used a fictional extremist website as the exposure condition, in which all participants accessed the website and the treatment was a mortality salience prime, which was assessed for its effects on participants' interactions with the site. Lemieux and Asal (2010) used a vignette design in which participants were asked to take a first‐person perspective as a member of a fictional ethnic minority.…”
Section: Resultsmentioning
confidence: 99%
“…Communication scholars and political scientists have already explored this subject tangentially. Scholars have long recognized the Internet as an attractive space for people and organizations with extremist viewpoints to recruit, organize, and radicalize others (Alvares and Dahlgren 2016; Graham 2016; Mott 2019; Post 2015; Richards 2019; Whine 1999a, 1999b), that people who spend a lot of time on the Internet can get exposed to extremist content quite easily (Costello et al 2016; Hassan et al 2018; Reeve 2019), and YouTube is no exception as a site of extremism, hate speech, and hostility (Costello et al 2016; Matamoros-Fernández 2017; Murthy and Sharma 2019; Schmitt et al 2018). However, beyond isolated case studies (Murthy and Sharma 2019), there is not much systematic evidence on engagement with the far right on YouTube.…”
Section: Situating Youtubementioning
confidence: 99%
“…Economic turmoil, particularly unemployment, has long been a pull factor for far-right groups and politicians (Arzheimer 2009;Bustikova 2014;Rydgren 2007). Men are also far more drawn to the far right than women are (Cohen et al 2018;Costello and Hawdon 2018;Reeve 2019). There has been a decades-long decline in the manufacturing sector in the United States, which has left many in the white working class, especially young men, without full employment (McDowell 2011).…”
Section: Demandmentioning
confidence: 99%
“…Different attitudes towards imposition and violence in radical and extremist groups have been observed in the literature (Altemeyer, 1981;Bötticher, 2017). Extremists' conception of politics tends to feel more comfortable with illiberal authorities (Altemeyer, 1981;Conway III et al, 2018) and prefer strict social hierarchies (Pratto et al, 1994;Reeve, 2021), which should make them overall more prone to prefer autocratic governance. By contrast, there are many examples of radical parties participating in the advancement of democracies (van Hiel et al, 2021).…”
Section: Political System Preferencementioning
confidence: 99%